Optimization of neural network with wavelet transform and improved data selection using bat algorithm for short-term load forecasting - Bento, P. M. R. (2019)
Submitted by CALADO (rc@ubi.pt) on 2019-07-22T15:50:05Z No. of bitstreams: 1 Neuro_2019.pdf: 3305888 bytes, checksum: dc3d40d04ec80f6d3be368e712cc3127 (MD5)